2001
DOI: 10.1017/s0263574700002939
|View full text |Cite
|
Sign up to set email alerts
|

Principles of superposition for controlling pinch motions by means of robot fingers with soft tips

Abstract: This paper analyzes the dynamics and control of pinch motions generated by a pair of two multi-degrees-of-freedom robot fingers with soft and deformable tips pinching a rigid object. It is shown firstly that passivity analysis leads to an effective design of a feedback control signal that realizes dynamic stable pinching (grasping), even if extra terms of Lagrange's multipliers arise from holonomic constraints of tight area-contacts between soft finger-tips and surfaces of the rigid object and exert to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(37 citation statements)
references
References 4 publications
(16 reference statements)
5
28
0
4
Order By: Relevance
“…The decoupling of total force and total moment stabilization also supports the principle of superposition suggested originally in robotics (Arimoto et al 2000(Arimoto et al , 2001. According to this principle, some actions by manipulators may benefit from having separate controllers for components of the action such as gripping (force production) and rotation action (moment production).…”
Section: Multi-digit Synergies Stabilizing the Total Momentsupporting
confidence: 60%
“…The decoupling of total force and total moment stabilization also supports the principle of superposition suggested originally in robotics (Arimoto et al 2000(Arimoto et al , 2001. According to this principle, some actions by manipulators may benefit from having separate controllers for components of the action such as gripping (force production) and rotation action (moment production).…”
Section: Multi-digit Synergies Stabilizing the Total Momentsupporting
confidence: 60%
“…To linearize the above equation we used the following experimentally established fact: humans control grasping force and rotational equilibrium of hand-held objects independently-the f G magnitude does not correlate with the moment that the f G generates (Shim et al 2003;Zatsiorsky and Latash 2004). This pattern of coordination exemplifies the principle of superposition suggested in robotics (Arimoto et al 2001). Following the principle of superposition for the handle shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Those studies have suggested that the control of two performance variables with the same set of effectors may be based on a principle of superposition (Arimoto et al 2001;Zatsiorsky et al 2004). According to this principle, separate controllers ensure co-variation within the same set of elemental variables that stabilizes each of the performance variables, and the effects of the two control signals sum up at the level of elemental variables.…”
Section: Stabilization Of Two Performance Variables By the Same Set Omentioning
confidence: 99%